Domain decomposition with the mortar cell method. (31st August 2013) - Moro, F.; Alotto, P.; Guarnieri, M.; Stella, A.; Dupre, Luc; Geuzaine, Christophe
ABSTRACT A novel domain decomposition technique is proposed in order to enforce either continuity or jump conditions on subdomain interfaces in nonconforming 2D discrete formulations, based on the cell method or the finite integration technique. Lagrange multiplier basis functions are proposed for an easy computation of the Schur complements in the partitioned linear system. Different matching and jump conditions are tested and compared on benchmark problems with analytical solutions. Copyright © 2013 John Wiley & Sons, Ltd.